MANAJEMEN PROGRAM SCHOOL GARDEN GUNA MEWUJUDKAN SEKOLAH ADIWIYATA - Indriani, Rakhmawati (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2018)
Abstract: The aims of this study are to describe the management of the School Garden program at SMAN 7 Malang, among others: the background; planning; implementation; evaluation; factors supporting and implementation of school garden programs as a form of Adiwiyata. Qualitative approach was used by case study design. Data were collected trough indepth interview, observation and documentation. The results of the application of the School Garden program can be seen from the achievements of the school after applying Adiwiyata program. The evaluation of the implementation of the School Garden program done directly, indirectly, and evaluation of the level-up which is expected to be used as benchmarks for principals and teachers in improving the management of the program. Implementation and management activities of the School Garden program is strongly influenced by the support and participation of all people in schools. Keywords: special service management, school garden, adiwiyata school.Abstrak: Penelitian ini bertujuan untuk mendiskripsikan manajemen program School Garden, antara lain: latar belakang; perencanaan; penerapan; evaluasi; faktor pendukung dan penghambat pelaksanaan program school garden di SMAN 7 Malang sebagai wujud program adiwiyata. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan studi kasus. Teknik pengumpulan data menggunakan wawancara mendalam, observasi, dan dokumentasi. Hasil penerapan program School Garden dapat dilihat dari prestasi yang telah diraih sekolah. Evaluasi terhadap penerapan program School Garden dilakukan secara langsung, tidak langsung, dan evaluasi tingkat lanjut (follow-up). Kegiatan pelaksanaan dan pengelolaan program School Garden sangat dipengaruhi oleh dukungan maupun partisipasi seluruh warga sekolah. Kata kunci: manajemen layanan khusus, School Garden, sekolah adiwiyata. DOI : 10.17977/um025v2i22018p089